Economic Sanctions and Trade Flows in the Neighbourhood - Vincenzo Bove; Jessica Di Salvatore; Roberto Nistico (Institute of Labor Economics (IZA), 2023)
We investigate the effect of economic sanctions on trade flows in countries sharing a border with sanctioned states. According to trade models, sanctions are expected to reduce trade flows as they disrupt established trading routes and economic relationships with suppliers and customers. However, there may also be instances where countries circumvent trade restrictions by clandestinely exchanging goods with sanctioned countries across the border and trading on their behalf, leading to an increase in imports and/or exports. To shed light on this issue, we employ a combination of large-N panel data analysis and comparative case studies using the synthetic control method. We find that, in the aggregate, neighbouring countries experience economic costs as sanctions disrupt trade. Yet, case studies uncover heterogeneity in countries' responses, with some cases exhibiting an increase in trade flows. We discuss possible explanations for these outcomes in the case-study analysis.
Keywords: F13; F14; F51; F52; K42; 330; economic sanctions; trade; sanctions-busting; land neighbours; smuggling; synthetic control method